Feminist Christians : a conflict resolved? : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Women's Studies at Massey University - Duncan, Anne Frances (Massey University, 1997)
This grounded theory study explains how women make meaning through their participation in the community of La Leche League New Zealand (LLLNZ). It is firmly situated within the context of the need to acknowledge and value women's experiential learning and knowledge, particularly that which occurs through the activities and relationships of motherhood. Seventeen women from throughout New Zealand participated in the study. Written narratives were gathered from eleven of these women and the remaining six took part in a group conversation. In addition, women's stories were collected from twelve months of issues of LLLNZ's journal for mothers. All data were constantly compared using Glaser's emergent approach to grounded theory. Analysis identified a three-stage process and three interacting voices, together creating a basic social process. This basic social process was conceptualised and integrated into a theoretical framework named integrating voices. It is argued that women make meaning through the process of integrating voices. This process comprises three intertwined stages, coming to know (voices), engaging with (voices) and voicing, and is integrative and recursive. The voices implicated throughout the three stages are a tripartite, representing a woman's own voice, the voices of others and the voice of the LLLNZ community. Integrating voices presents an integrated model of meaning-making. The model is integrated through its three-stage process as well as through its tripartite voices. Five strong threads weave through all dimensions and processes of the model. These are: body, mind and emotions; relationships; narrative/story; identity and the practice of the community. The grounded theory integrating voices offers a holistic explanation of learning. It proposes an integration of mind, body and emotions, within the individual and the social, and embedded in context. Additionally, it emphasises that significant learning takes place within everyday activities and in the practice of those everyday activities. These findings have implications for adult education theory and practice where there is a need for a shift towards more inclusive and holistic accounts of adult(s) learning.
Keywords: Feminism; Religious aspects; Christianity; New Zealand; Patriarchy; Women in Christianity